(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
The purpose of the current research is to determine the role of the economic situation of small and medium-sized enterprises in Egypt, Saudi Arabia, and the United Arab Emirates, in achieving sustainable development. Small and medium-sized enterprises represent a major driver of the economy in any of these countries, given their significant role in building and improving living standards and reducing the high unemployment rates experienced by most countries. Furthermore, they encourage innovation and improve business levels. To achieve this, the current research employed a descriptive analytical approach to collect the necessary data from these enterprises for the period (2010-2024). In addition, secondary data derived from financial reports and relevant economic statistics pertaining to small and medium-sized enterprises in the sample countries were analysed. The research yielded several findings, the foremost of which is that small and medium-sized enterprises in the concerned countries contribute to building the national economy by addressing and confronting key challenges, particularly regarding funding shortages and the obstacles to accessing markets, The results indicate a significant disparity between the effectiveness of these projects and the capabilities contained within them to achieve sustainable development goals among the targeted sectors. Based on this, the research recommends that the mentioned countries should work on improving their business environment by providing financial, technical, and professional support through the development of innovation and fair competition, as well as enhancing cooperation between these sectors at both the public and private levels to ensure the attainment of sustainable development goals